Employee Performance Improvement Strategy in the Manufacturing Industry - Rahman Soesilo; Lucy Lidiawati Santioso; Kamsariaty Kamsariaty; Dian Nur Mastuti; Rohana Sitanggang (Greenation Publisher & Yayasan Global Research National, 2024)
Abstract: Article Employee performance improvement strategy at the manufacturing industry within the scope of human resource management science. This article aims to create hypotheses regarding the relationship between factors, which can then be used for further research in the field of human resource management. The research method used in this research is descriptive qualitative. The data used in this research comes from previous research which is still relevant to the current investigation. Data was collected from leading academic online platforms, including Publish or Perish, Google Scholar, digital reference books, and Sprott journals. The results of this literature research include 1) The influence of self-efficacy on employee engagement; 2) The influence of psychological tests on employee engagement; 3) The influence of work life balance on employee engagement; 4) The effect of remuneration on employee engagement; 5) The influence of self-efficacy on employee performance; 6) The influence of psychological tests on employee performance; 7) The influence of work life balance on employee performance; 8) The effect of remuneration on employee performance; and 9) The influence of employee engagement on employee performance. Keyword: Employee Performance, Employee Engagement, Self Efficacy, Psychology Test, Work-Life Balance, Remuneration